1995
DOI: 10.1159/000096889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citrus Fragrance on Immune Function and Depressive States

Abstract: In our previous experiments on animals evidence was found that citrus fragrance can restore the stress-induced immunosuppression, suggesting that citrus fragrance may have an effect on restoring the homeostatic balance. Since a dysregulation of the neuroendocrine and immune function is thought to be associated with psychosomatic or psychiatric disorders an attempt was made to restore their mental health by stimulation of one of the sensory systems. Fragrance (citrus was our choice) which comforts through stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 1 publication
2
114
0
3
Order By: Relevance
“…This view can help to explain the surprisingly positive results found in the treatment of depression with aromatherapy and essential oils [14], specially by using lemon citrus fragrance [2]. This hypothesis has been corroborated by results obtained with a rat experimental model of MDD [3].…”
Section: Brain Metabolism and Aromatherapymentioning
confidence: 53%
See 1 more Smart Citation
“…This view can help to explain the surprisingly positive results found in the treatment of depression with aromatherapy and essential oils [14], specially by using lemon citrus fragrance [2]. This hypothesis has been corroborated by results obtained with a rat experimental model of MDD [3].…”
Section: Brain Metabolism and Aromatherapymentioning
confidence: 53%
“…In this paper, we attempt to move one step forward in this line of research, by making a hypothesis that has practical implication for psychotherapy. We restrict our hypothesis to vanillin and citrus fragrances because encouraging experimental results have been found with lemon odors [2,3] and vanillin [4] using the rat model of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70][71] A meta-analysis of 14 published trials however concluded that serum anti-ribosomal P measurements were not sensitive in diagnosing NPSLE and did not distinguish between NPSLE subsets. [72][73][74][75][76] The few pediatric NPSLE studies so far have only demonstrated a higher prevalence of these and anti-dsDNA and anti-Sm antibodies, in childhood than adult onset SLE without any clear causal or pathogenic association yet elucidated. 4,77,78 Our group at University College London (UCL), recently described the observation that serum anti-Sm antibodies levels correlate positively with higher levels of nitrated nucleosomes, a serum marker of nitrosative stress, as measured by a novel capture ELISA.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Citrus fragrance was given to depressive human subjects and the results indicated that the doses of antidepressants necessary for the treatment of depression could be markedly reduced. The treatment with citrus fragrance normalised neuroendocrine hormone levels and immune function and was rather more effective than antidepressants [15].…”
Section: Introductionmentioning
confidence: 97%
“…Certain odours can ameliorate depression and anxiety; for example, work on animals has shown that citrus fragrance can restore stressinduced immunosuppression [13,14] and lemon odour was found to be antidepressant in rats [15]. In normal human subjects, lemon odour reliably enhanced positive mood [16] and negative emotions became less intense during exposure to citrus odour [17].…”
Section: Introductionmentioning
confidence: 99%